1980
DOI: 10.1093/clinchem/26.11.1620
|View full text |Cite
|
Sign up to set email alerts
|

Detection of alkaline phosphatase/immunoglobulin complexes.

Abstract: We report another patient with a circulating alkaline phosphatase/immunoglobulin complex in his blood, and describe a simple method of demonstrating such complexes. On electrophoresis on cellulose acetate, the complex was relatively slow moving and there was no activity in the normal bone/liver isoenzyme region. When the serum was treated with trypsin, the slow band disappeared and the normal pattern was restored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Reported macro-ALP were bound to IgG [6,7] and to a lesser extent IgA [8,9]. e ALP is usually of liver and bone origin or both [10]. Gel filtration analysis of the macro-ALP suggested that the results will be consistent with equimolar complexes of IgG-ALP or a complex made up of two molecules of IgG with one of ALP or one molecule of IgG and two molecules of ALP [6].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Reported macro-ALP were bound to IgG [6,7] and to a lesser extent IgA [8,9]. e ALP is usually of liver and bone origin or both [10]. Gel filtration analysis of the macro-ALP suggested that the results will be consistent with equimolar complexes of IgG-ALP or a complex made up of two molecules of IgG with one of ALP or one molecule of IgG and two molecules of ALP [6].…”
Section: Discussionmentioning
confidence: 95%
“…is method will not detect complexes to immunoglobulins other than IgG so has limitations [10]. In a further case study, Nagakawa et al [13] reported an intestinal ALP-IgG complex in which the IgG had the ability to inhibit ALP in a patient's serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline values for serum-biochemical parameters were determined before the commencement of the experiment, according to standard procedures (Barham and Trinder, 1972;Patton and Crouch, 1977;Buttery et al, 1980;Grant, 1987). Blood samples were collected via the wing vein, using 25 gauge sterile hypodermic needles and syringes and then kept in a slanted position for serum to settle.…”
Section: Determination Of Serum Biochemical Parametersmentioning
confidence: 99%
“…This was done using the method of Buttery et al (1980). 500µl of blank; standard and sample was pipette into test tube and incubated at 37°C for 10 minutes, after which 2500µl of alkaline phosphatase colour developer was added into each of the test tubes, mixed and then the absorbance was read using a spectrophotometer at wavelength of 590nm.…”
Section: Assay For Serum Alkaline Phosphatase (Alp)mentioning
confidence: 99%